2013
DOI: 10.1128/jb.00265-13
|View full text |Cite
|
Sign up to set email alerts
|

Complex Regulation of the Phosphoenolpyruvate Carboxykinase Gene pck and Characterization of Its GntR-Type Regulator IolR as a Repressor of myo-Inositol Utilization Genes in Corynebacterium glutamicum

Abstract: c DNA affinity chromatography with the promoter region of the Corynebacterium glutamicum pck gene, encoding phosphoenolpyruvate carboxykinase, led to the isolation of four transcriptional regulators, i.e., RamA, GntR1, GntR2, and IolR. Determination of the phosphoenolpyruvate carboxykinase activity of the ⌬ramA, ⌬gntR1 ⌬gntR2, and ⌬iolR deletion mutants indicated that RamA represses pck during growth on glucose about 2-fold, whereas GntR1, GntR2, and IolR activate pck expression about 2-fold irrespective of wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 84 publications
1
49
0
Order By: Relevance
“…Unlike Bifidobacterium species, in L. casei the gnb cluster containing the genes involved in the metabolism of those disaccharides does not encode sugar kinases. We showed that the genes gnbF, encoding GalNAc-6P deacetylase, and nagA, encoding GlcNAc-6P deacetylase, were involved in the metabolism of GNB and LNB, respectively, which indicates that the GalNAc and GlcNAc resulting from (Hu et al, 1989); FarR (Quail et al, 1994); TreRo1 and TreRo2 (Schöck and Dahl, 1996); KorSA (Sezonov et al, 2000); NagRdre nagP and NagRdre nagA (Bertram et al, 2011); PckR (Hyeon et al, 2012); IolR (Klaffl et al, 2013). Bases conserved in all sequences are shown against a dark background.…”
Section: Et Al 2009mentioning
confidence: 99%
“…Unlike Bifidobacterium species, in L. casei the gnb cluster containing the genes involved in the metabolism of those disaccharides does not encode sugar kinases. We showed that the genes gnbF, encoding GalNAc-6P deacetylase, and nagA, encoding GlcNAc-6P deacetylase, were involved in the metabolism of GNB and LNB, respectively, which indicates that the GalNAc and GlcNAc resulting from (Hu et al, 1989); FarR (Quail et al, 1994); TreRo1 and TreRo2 (Schöck and Dahl, 1996); KorSA (Sezonov et al, 2000); NagRdre nagP and NagRdre nagA (Bertram et al, 2011); PckR (Hyeon et al, 2012); IolR (Klaffl et al, 2013). Bases conserved in all sequences are shown against a dark background.…”
Section: Et Al 2009mentioning
confidence: 99%
“…Seventy genes were upregulated more than 1.5-fold, whereas 229 genes were downregulated more than 1.5-fold (see Table S2 in the supplemental material). Decreased expression of ptsG and pckA and increased expression of tkt, gnd, gntK, gntP, and gntV were observed as described previously (13)(14)(15). In addition to these genes, we found that the expression of many of the genes involved in carbon metabolism was changed; these genes are gapB, rbsK2, rbsK1, dctP2, ugpE, dhaS, maeB, dctA, dctM1, dctP1, bglF2, and bglF.…”
Section: Identification Of In Vivo Binding Sites Of Gntr1mentioning
confidence: 79%
“…GntR1/2 is known to control the expression of genes of gluconate utilization (gntP and gntK), the pentose phosphate pathway (tkt, tal, zwf, opcA, devB, and gnd), the phosphotransferase system (ptsG and ptsS), and gluconeogenesis (pckA) in C. glutamicum ATCC 13032, indicating that GntR1/2 is one of the important transcriptional regulators for carbon metabolism (13)(14)(15). In C. glutamicum R, the gntR2 gene is missing and gntR1 is solely responsible for the induction of the gnd gene by gluconate (14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations